2021
DOI: 10.1097/dad.0000000000002064
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Reflectance Confocal Microscopy of Adnexal Tumors: Evaluation of Trichoepithelioma, Sebaceoma, and Fibrofolliculoma

Abstract: :Cutaneous adnexal tumors are benign and malignant neoplasms that undergo morphological differentiation into cutaneous adnexa, comprising pilosebaceous, eccrine, or apocrine units. Reflectance confocal microscopy is a noninvasive diagnostic method that enables in vivo visualization of tissues at a similar resolution as conventional histopathology. The use of this method in skin imaging over the past several years has improved dermatological diagnoses, potentiating its wide application, especially for benign an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…The presence of sebocytes with central dark nuclei and abundant cytoplasm filled with bright fine granules is a crucial clue to differentiate sebaceoma from BCC. 6 , 7 Surprisingly, no obvious sebocytes were found under RCM in our case. IN our experience, the refractive index of sebocytes is not as high as that of dendritic cells on RCM, and sebocytes only account for a small proportion of the tumor, these lead to difficulties to visualize sebocytes when numerous dendritic cells present within the tumor.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…The presence of sebocytes with central dark nuclei and abundant cytoplasm filled with bright fine granules is a crucial clue to differentiate sebaceoma from BCC. 6 , 7 Surprisingly, no obvious sebocytes were found under RCM in our case. IN our experience, the refractive index of sebocytes is not as high as that of dendritic cells on RCM, and sebocytes only account for a small proportion of the tumor, these lead to difficulties to visualize sebocytes when numerous dendritic cells present within the tumor.…”
contrasting
confidence: 55%
“…reported that sebaceomas lack space between the tumor and the stroma. 7 However we observed this structure, only the dark space was narrower than in BCC. The presence of sebocytes with central dark nuclei and abundant cytoplasm filled with bright fine granules is a crucial clue to differentiate sebaceoma from BCC.…”
mentioning
confidence: 51%
“…Additionally, we did not examine the diagnostic significance of alternative imaging modalities in differential diagnosis of BCC and TT. Previous studies suggested possible utility of in vivo reflectance confocal microscopy (RCM), optical coherence tomography, as well as high-frequency ultrasound examination [ 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%